1978
DOI: 10.1042/bj1740585
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipid components of the diet in the regulation of the fatty acid composition of the rat liver endoplasmic reticulum and lipid peroxidation

Abstract: The fatty acid compositions of the lipids and the lipid peroxide concentrations and rates of lipid peroxidation were determined in suspensions of liver endoplasmic reticulum isolated from rats fed on synthetic diets in which the fatty acid composition had been varied but the remaining constituents (protein, carbohydrate, vitamins and minerals) kept constant. Stock diet and synthetic diets containing no fat, 10% corn oil, herring oil, coconut oil or lard were used. The fatty acid composition of the liver endopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(45 citation statements)
references
References 24 publications
3
39
2
1
Order By: Relevance
“…Selenium-deficient rats from these two diet groups were given diquat. Rats fed the corn oil diet produced one-third as much ethane as those fed the cod liver oil diet, presumably because their tissues contained less omega-3 polyunsaturated fatty acid (20,21). However, evidence of liver and kidney necrosis was unaffected by the diet.…”
Section: Resultsmentioning
confidence: 87%
“…Selenium-deficient rats from these two diet groups were given diquat. Rats fed the corn oil diet produced one-third as much ethane as those fed the cod liver oil diet, presumably because their tissues contained less omega-3 polyunsaturated fatty acid (20,21). However, evidence of liver and kidney necrosis was unaffected by the diet.…”
Section: Resultsmentioning
confidence: 87%
“…The lack of a statistically significant difference between high-fat diet and the control diet in biochemical and histopathological examination, suggest that oleic acid which has been in high fat diet content of soybean oil (13) and lard (14) would have protective effect (15). In another study, it was found that soybean oil decrease lipogenesis and liver fat density (16).…”
Section: Discussionmentioning
confidence: 99%
“…Peroxidation of lipids is associated with oxygen toxicity and causes degeneration of cell membranes and other lipid-containing structures, and thus is closely associated with pathologies. 5) We have shown in previous studies that the ingestion of DHA, [6][7][8][9][10] as with the ingestion of fish oil, [11][12][13][14] enhanced the susceptibility of rat liver and kidney to lipid peroxidation and increased the requirement for vitamin E (VE). This enhanced lipid peroxidation was a function of the dietary DHA level and was thought to be attributable to the replacement of membrane fatty acids with highly unsaturated DHA.…”
Section: -4)mentioning
confidence: 99%